Enhancing accessibility: assistive devices pairing mobile apps for visually impaired people - Ibrahim, Aisyah; Toha, Siti Fauziah; Nordin, Nor Hidayati Diyana; Tokhi, Mohammad Osman (UTP Press, 2023)
Vision impairment and blindness are significant health conditions that affect a considerable portion of the global population and have significant consequences, particularly in developed nations. Its harmful consequences can have a negative influence on a person's personal quality of life, as well as limit their ability to live independently. Navigation plays a crucial role in the activities that are impacted by vision loss. This is because it is almost impossible for the individual to move safely and independently. The goal of this project is to improve mobility for visually impaired people by employing Light Detection and Ranging (LiDAR) sensors to identify obstacles and alert users via haptic feedback if there are potential obstacles in their way. In addition, this study compares two sensors, LiDAR and ultrasonic sensors, besides the implementation of the Internet of Things (IoT), which was integrated into the small, portable robot by pairing a mobile phone. This is to ensure the user may be securely guided to their destination. I-Walk is a mobile app with a voice user interface (VUI) for global positioning system (GPS) navigation systems and emergency calling. This app has been developed to allow users safe and independent travel. The simulation result shows that even though ultrasonic sensors are cheaper and serve the same function as LiDAR, their huge standard deviation and percentage error shown in this study cannot equal LiDAR's accuracy in which LiDAR has an average error of 0.63%. In contrast, ultrasonic sensors have an average error of 2.39%. Overall, this obstacle detection and navigation system comprises robust hardware and software to assist visually impaired people effectively.